Design and analysis of limited angle torque motor for electric vehicle applications - Lei, Xiaoyi (Nanyang Technological University, 2023)
Actuators are essential components used for controlling and moving systems in various scenarios, including transportation vehicles, industrial machine tools, and common equipment. Traditional actuation systems relied on mechanical, hydraulic, and pneumatic solutions. However, these solutions have limitations that can reduce system reliability and torque density, especially in the context of global electrification. To overcome these limitations, the limited angle torque motor (LATM) has been proposed as a new electric solution. The LATM is designed to swing within a limited angular range while outputting a constant torque, with a simplified control circuit that enhances system reliability. The LATM design is suitable for various high-performance and reliability applications such as miniature robot joint drives and aerospace servo valves. This thesis proposes a new motor structure based on finite element analysis and J-MAG DESIGNER to enhance actuation system performance. The proposed LATM design offers superior torque density, efficiency, reliability, and dynamic response, making it a promising solution for future research and development. The motor design utilizes the virtual work principle and tapered tooth-tip to output a constant torque within the operating range. The topology of the permanent magnet and tooth-tip had a significant impact on the output torque, as determined through detailed simulations. The final design achieved a 40° operating range under standard conditions, with an average output torque of 0.2157 Nm and fluctuations of less than 4.08%. The proposed design approach for LATMs enhances the performance of actuation systems, demonstrating the limitations of traditional solutions. In conclusion, the study proposes a novel design approach for LATMs that enhances the performance and reliability of actuation systems. The achieved outcome of this study demonstrates that the proposed LATM design is a promising solution for a range of actuation system applications. Key word: limited angle torque motor, FEA, cogging torque, electric vehicle, BLDC